Healthcare delivery reform and new technologies : organizational initiatives - Guah, Matthew (Medical Information Science Reference, 2011)
"This book contains cross-disciplinary research on strategic initiatives for healthcare reform that impact not only patients, but also organizations, healthcare providers, and policymakers"--Provided by publisher.